Infrequent chemoradiation‐induced acute esophagitis in the Asian population: A meta‐analysis of published clinical trials for unresectable stage III non‐small cell lung cancer. Issue 6 (November 2014) - Komiya, Takefumi; Palla, Shana L.; Wang, Feng; Perez, Raymond P.; Huang, Chao H.
Abstract Severe (grade 3 or higher) esophagitis is one of the major toxicities for chemoradiation in the treatment of stage III non‐small cell lung cancer (NSCLC). The difference among ethnic groups has never been investigated in detail. Prospective trials with concurrent platinum‐containing chemoradiation in unresectable disease were investigated, and a total of 116 treatment arms with 7520 patients were identified. Univariate analysis demonstrated that treatment arms conducted in Asia had significantly lower incidence of severe esophagitis (170/2534, 6.7%, odds ratio 0.289) than in other nations (1025/4986, 20.6%). In the multivariable model, Asian/non‐Asian ethnicity, multi‐/single‐agent, and split are jointly significant predictors after adjusting for all possible factors. This study suggests that severe esophagitis occurs less frequently in the Asian population compared to the non‐Asian population.